Politicas públicas para agricultura familiar: o caso do Programa de Aquisição de Alimentos (PAA) no estado de São Paulo, Brasil - Oliveira, Jonatan Alexandre de [UNESP] (2016)
The general purpose of this work is to evaluate, in the period 2003-2012, the implementation of the Family Agriculture Food Acquisition Program (PAA) by the regional office of the National Supply Company (Conab) in Sao Paulo, trying to relate their distribution in agrarian space state with economic indicators, political and social rights of their farmers. Specifically, we compare the action of Conab / SP with other regional offices; It studies the performance of two types of EAP, Purchase with Simultaneous Donation and the Inventory Training for Family Agriculture assesses the social impact of the program, in terms of family farmers and people in processed food insecurity; It relates to the spatial distribution of PAA with the relative importance of family farmers, with the development index of the São Paulo regions with the existence of agrarian reform settlements and the implementation of the National Family Farming Strengthening Program (PRONAF). Regarding the methodology, we carried out a survey on the main public policies for family farming such as PRONAF, PAA and National School Feeding Programme (PNAE). Subsequently made up evaluative study of secondary data associated with documentary research. For secondary data sought up information from the federal and state agencies linked to agricultural and land issues. With regard to the documentary research was rated a set of texts and reports from the Federal Government, with emphasis on Balance Assessment Implementation of 2003-2012 Food Acquisition Program of the Department of Evaluation and Management of Information of the Ministry of Social Development and Fight against Hunger. The first part of the work delas with the historical background of policies that worked in the conformation of the Brazilian agricultural land between 1960 and 1990, when there was exclusion of family farming, followed by a relative reversal from the creation of PRONAF in 1996. This specific attention to family farming has been strengthened with the creation of the PAA in 2003, which currently has six different modes and seeks the development of equitable rural areas, encouraging the marketing and income generation for family farmers, while benefiting people in a situation of food insecurity. The second part deals with the implementation of the AAP between 2003 and 2012 in the Brazilian agricultural space, taking into account regional disparities in the country. In the third part analyzes the implementation and distribution of PAA in São Paulo, and may be related some results. CONAB / SP has shown relative performance better than all the other regional offices; Purchase with Simultaneous Donation mode reaches more significant number of municipalities; PAA has been applied with greater intensity in favor of family farmers and settlers of the poorest regions; there is a strong bond of PAA with the agrarian reform settlements; PAA appears to complement the PRONAF, in that it serves more intensely precisely those farmers with greater difficulties of access to rural credit program.